2008
DOI: 10.1111/j.1462-5822.2008.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

The MACPF/CDC family of pore-forming toxins

Abstract: SummaryPore-forming toxins (PFTs) are commonly associated with bacterial pathogenesis. In eukaryotes, however, PFTs operate in the immune system or are deployed for attacking prey (e.g. venoms). This review focuses upon two families of globular protein PFTs: the cholesterol-dependent cytolysins (CDCs) and the membrane attack complex/perforin superfamily (MACPF). CDCs are produced by Gram-positive bacteria and lyse or permeabilize host cells or intracellular organelles during infection. In eukaryotes, MACPF pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
208
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(210 citation statements)
references
References 76 publications
1
208
0
1
Order By: Relevance
“…30 Furthermore, the lack of sequence similarity with other structurally characterized proteins also delayed progress. However, in the year 2007-2008, three independent studies arrived at the same remarkable conclusion: despite sharing minimal amino acid sequence similarity, mammalian and other MACPF proteins are structurally related to bacterial cholesterol-dependent cytolysins (CDCs) and operate by an analogous mechanism.…”
Section: Perforin Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, the lack of sequence similarity with other structurally characterized proteins also delayed progress. However, in the year 2007-2008, three independent studies arrived at the same remarkable conclusion: despite sharing minimal amino acid sequence similarity, mammalian and other MACPF proteins are structurally related to bacterial cholesterol-dependent cytolysins (CDCs) and operate by an analogous mechanism.…”
Section: Perforin Biologymentioning
confidence: 99%
“…The predicted similarity between bacterial CDCs and MACPF proteins strongly suggested that PRF pore formation would require major conformational changes, which would only be possible in structurally labile proteins. 30 We therefore hypothesized that cancer-associated mutations, such as A91V, might predominantly result in misfolding rather than loss of function per se. Indeed, by reducing the culture temperature of mutant PRF-expressing cells to 301C to optimize folding, we showed that the activity of most of the mutants could be restored to a significant extent.…”
Section: Perforin Deficiency and Human Cancermentioning
confidence: 99%
“…2 This is followed by oligomerization into a large circular pre-pore by lateral interactions of the monomers followed by conformational change of the central MACPF domain, resulting in membrane insertion and formation of a large ÎČ-barrel pore of ~100 Å diameter. 18 Functions of these pores include: (1) killing target cells by disrupting their outer membrane as is the case for many bacterial CDCs as well as components of the membrane attack complex (C6-C9); 2 (2) delivering other effector proteins across membranes as in the delivery of granzyme by perforin; 3 or (3) facilitating pathogen traversal of a membrane barrier as in the case of Listeriolysin O mediated release from the phagosome.…”
Section: Functionmentioning
confidence: 99%
“…2 These pre-pores undergo a molecular rearrangement and insert into target membranes to form large pores (~100 Å diameter). 2,3 Exciting work over the past couple of years has provided additional insight into their molecular mechanism of action by revealing that the MACPF fold is shared with that of the cholesterol-dependent cytolysins (CDCs), an extensively studied family of bacterial pore-forming virulence factors. 4,5 Here we present an overview of the Apicomplexan PerforinLike Proteins (ApiPLPs) that have been identified in parasites for which genome sequence is available.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, work in vertebrates has revealed that CDCs and membrane attack complex/perforin superfamily domain-containing proteins share a similar fold, suggesting that vertebrates use a similar mechanism for defense against infection (1,2). A common feature of the CDC family is the requirement of cholesterol in the membrane to form pores (3).…”
mentioning
confidence: 99%